Cross-sectional studies in occupational health research: An overview of strengths and limitations - Francesco CHIRICO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2023)
Cross-sectional study design, a prominent aspect of observational research, facilitates the simultaneous assessment of outcomes and exposures among study participants. Unlike case-control or cohort studies, cross-sectional investigations select participants based on predetermined inclusion and exclusion criteria rather than outcome or exposure statuses. Once the participant cohort is established, the study evaluates exposure and outcome relationships. This design finds application in population-based surveys and the assessment of disease prevalence within clinic-based samples. The efficiency and cost-effectiveness of cross-sectional strategies make them appealing for preliminary data collection before embarking on cohort studies, thus providing a foundational basis for subsequent cohort study planning. While offering insights into outcome and exposure prevalence, the inherent limitation of single-time exposure and outcome measurement in cross-sectional analysis hinders establishing causal relationships. Nevertheless, cross-sectional studies enable the estimation of disease prevalence and odds ratios, facilitating the exploration of exposure-outcome associations. This paper comprehensively elucidates the utilization of cross-sectional studies in occupational health, emphasizing strengths and limitations and highlighting their significance in shaping research methodologies and informing future investigations in this discipline.